Human capital and economic growth: secondary school or higher school? - N., Shalini; Abdul Hamid, Baharom; Kaur, Harpaljit; Habibullah, Muzafar Shah; Mohd Yunus, Rossita (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This study investigates the linkages between economic growth and human capital. It employs the dynamic panel system GMM estimators, focusing on secondary school and higher school education as the proxy for human capital. The data was averaged to 7 points based on a sample of 62 countries spanning from year 1970 - 1999. The data was extracted from the World Development Index 2007 and study by Barro and Lee (2010). The results are particularly interesting, contrary to the expectation; only the high school graduates affect the growth while the secondary school graduates show insignificant. With disaggregation of countries based on the stages of economic development, high school show greater effect. These results further strengthens the grounds that human capital is indeed an important component and acts as an engine for economic growth.